Improving Pronunciation Skills through English Songs for Junior High School Students - Siki, Veliana; Pale, Erlinda Sonya; Abi, Benyamin Kau (International Journal of English Education and Linguistics (IJoEEL), 2024)
This study entitled “Improving Students’ Speaking Skills Through English Songs For The Eight Grade Students Of Smp Negeri Oenenu In The School Year 2023/2024.” The purpose of this study are: 1) To know how english songs improve speaking skills of SMP Negeri Oenenu. 2) To know the problems faced by the students in using english songs to improve their speaking skills by conducting Classroom Action Research (CAR). The subjects of this research is eighth grade students at SMP Negeri Oenenu which consisted of 25 students and was conducted in two cycles. The instrument of collecting data was oral test, observation, and interview. Based on data analysis, the score of students’ oral Test improved in every test. In the result of students’ tests were showed that the mean score of pre-tests was 64,2. The mean score of the test in cycle I was 72. The mean score of the tests in Cycle II was 79. Based on observation sheet, it was found that teaching learning process ran well. After giving the treatment by listening to English songs, the students’ English Pronunciation in pronouncing English words improved. It was concluded that listening to English songs can improve the students’ English Pronunciation.